Effect of Avocado Seed Extract through Milling on Reducing Triglyceride in Hyperlipidemic Rats - Rita Dewi Firmansyah; Jojor Lamsihar Manalu; Yulia Tanti Narwati; Maria Dara Novi Handayani; Alexander Yose Ardin Bagas Sulistyo (School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, 2023)
Background : Hypertriglyceridemia is a condition in which there is an increase in triglycerides in the blood. This increase is influenced by foods that contain extra calories. Hypertriglyceridemia can cause disturbances in the body in the form of cardiovascular disease. Methods : The study used experimental methods on male Sprague Dawley rats. The research sample used fourteen rats which were divided into a control group and a treatment group. All experimental mice were induced to become hyperlipidemic by PTU14 gram/kg for 14 day. The control group was not given any treatment. The treatment group was given avocado seed extract 250 mg/kg for 14 day. Avocado seed extract is obtained through crushing and extraction processes. The statistic we used in this study is paired T-test. Results : In the control group, there was no decrease in triglyceride levels with an average of 134.78 mg / dL. In the treatment group there was a decrease in the average triglyceride levels both after seven days of giving avocado seed extract on (day 28) 127.92 md / dL and after fourteen days of giving avocado seed extract on (day 35) 124.21 mg / dL. Conclusion: Giving of avocado seed extract by grinding method for 30 minutes selama sekian hari had an effect in reducing triglyceride levels in hyperlipidemic rats. Keywords: Avocado Seed Extract - Sprague Dawley Rats - Triglyceride Level.